Microencapsulation of Fermented Red Palm Oil with L. casei as Nutracetical Source - Hertanti, Hertanti; Nuralang, Nuralang; Susanto, Nindita Clourisa Amaris; Tarigan, Indra Lasmana; Nelson, Nelson (Jurnal Rekayasa Kimia & Lingkungan, 2022)
Red Palm Oil (RPO) is the result of refining from Crude Palm Oil (CPO) which still maintains a high level of phytonutrients that are beneficial for health. The benefits of RPO can be used as a nutraceutical source, because RPO acts as a provitamin A and vitamin E. The addition of Lactic Acid Bacteria (LAB) in a product functions as a probiotic with metabolite activity that can inhibit pathogenic microorganism thereby increasing the durability of a product. The addition of LAB to RPO is expected to increase the nutraceutical value by adding probiotic properties to RPO products. Microencapsulation technology can protect the bioactive content of essential oils against unwanted chemical interactions with other components and provide increased stability during processing. This research is expected to be able to provide information about the potential raw material of fermented RPO as a nutraceutical source by showing the profile of RPO before and after the fermentation process, chemical and physical properties of the microencapsulant. The microencapsulation technique used is the extrusion method. Fermentation of the bioactive compound ingredients in RPO using L. casei has a significant effect. RPO after fermentation using L. casei (Red-PalmZym) produces major compounds in the form of 9-Octadecenoic acid, methyl ester, (E)- Fermentation of RPO with L. casei increases the components of chemical compounds contained therein. The stability of the RPO microencapsulated before fermentation provided an effective protection against oxidative damage to the oil and proved that the microencapsulation process can reduce the level of damage to the oil.